Indonesian Democracy: Democracy without the Public - Sugeng Bayu Wahyono (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2024)
Since its independence, the Republic of Indonesia has been a democratic and unitary state. However, democracy has had its ups and downs and been influenced by the characteristics of the leaders from the era of President Soekarno, New Order, to the reform era. This study employed the reflective method to analyse the political phenomena of contemporary Indonesia, based on empirical facts and academic information. This study discusses the issue of democracy. Instead of the role of the middle class or global political constellation, it focuses on the failure of the political process to shape the public, a prerequisite for implementing democracy. This research reveals that three strategic social institutions in the dynamics of contemporary Indonesian politics, namely religion, bureaucracy, and educational institutions also fail to shape the public. It leads to formal, procedural, and less substantive democracy in Indonesia. Therefore, the people need a democracy literacy movement through various strategic social and political institutions.